Risk of death following pregnancy in rural Nepal - Pradhan Elizabeth Kimbrough; West Jr Keith P.; Katz Joanne; Christian Parul; Khatry Subarna K.; LeClerq Steven C.; Dali Sanu Maiya; Shrestha Sharada Ram (The World Health Organization, 2002)
OBJECTIVE: To investigate the length of time following pregnancy during which the risk of mortality was elevated among women in rural Nepal. METHODS: An analysis was performed of prospective data on women participating in the control group of a large, population-based trial. Weekly visits were made for three years to 14 805 women aged 14-45 years. Pregnancy and vital status were assessed. A total of 7325 pregnancies were followed. Mortality during and following pregnancy, expressed on a person-time basis, was compared to referent mortality unrelated to pregnancy (52 weeks after pregnancy) in the same cohort. FINDINGS: The relative risk (RR) of death during pregnancy but before the onset of labour was 0.93 (95% confidence interval (CI): 0.38-2.32). During the perinatal period, defined as lasting from the onset of labour until seven days after outcome, the RR of death was 37.02 (95% CI: 15.03-90.92). The RR for 2 to 6 weeks, 7 to 12 weeks, and 13 to 52 weeks after pregnancy were 4.82, 2.59 and 1.01 with 95% CI of 1.77-13.07, 0.81-8.26 and 0.40-2.53, respectively. The RR of death was 2.21 (95% CI. 1.03-4.71) during the conventional maternal mortality period (pregnancy until 6 weeks after outcome). It was 2.26 (95% CI: 1.05-4.90) when the period was extended to 12 weeks after pregnancy outcome. CONCLUSION: The risk of mortality associated with pregnancy should be assessed over the first 12 weeks following outcome instead of over the first 6 weeks.